Bovine endometrium responds differentially to age-matched short and long conceptuses†. Issue 1 (12th April 2019) - Sánchez, José María; Mathew, Daniel J; Behura, Susanta K; Passaro, Claudia; Charpigny, Gilles; Butler, Stephen T; Spencer, Thomas E; Lonergan, Pat
Abstract: This study combined in vitro production of bovine blastocysts, multiple embryo transfer techniques, and a conceptus-endometrial explant co-culture system to test the hypothesis that bovine endometrium exposed to long vs. short day 15 conceptuses would exhibit a different transcriptome profile reflective of potential for successful pregnancy establishment. Bovine endometrial explants collected at the late luteal stage of the estrous cycle were cultured in RPMI medium for 6 h with nothing (control), 100 ng/mL recombinant ovine interferon tau (IFNT), a long day 15 conceptus, or a short day 15 conceptus. Transcriptional profiling of the endometrial explants found that exposure of endometrium to IFNT, long conceptuses, or short conceptuses altered ( P  < 0.05) expression of 491, 498, and 230 transcripts, respectively, compared to the control. Further analysis revealed three categories of differentially expressed genes (DEG): (i) commonly responsive to exposure to IFNT and conceptuses, irrespective of size (n = 223); (ii) commonly responsive to IFNT and long conceptuses only (n = 168); and genes induced by the presence of a conceptus but independent of IFNT (n = 108). Of those 108 genes, 101 were exclusively induced by long conceptuses and functional analysis revealed that regulation of molecular function, magnesium-ion transmembrane transport, and clathrin coat assembly were the principal gene ontologies associated with these DEG. In conclusion, bovine endometrium responds differently to age-matched conceptuses of varying size in both an IFNT-dependent and -independent manner, which may be reflective of the likelihood of successful pregnancy establishment. Abstract : Bovine endometrium responds differently in terms of its gene expression signature to age-matched conceptuses of varying size, in both an interferon-dependent and independent manner, which may be reflective of the likelihood of successful pregnancy establishment.